A novel methodology for shear cohesive law identification of bonded reinforcements. (1st July 2018) - Perrella, M.; Berardi, V.P.; Cricrì, G.
Abstract: Repair of structural elements with bonded fiber reinforced polymers (FRPs) is widely used in many engineering applications. Within the strengthening of civil structures, failure usually occurs due to FRP debonding by in-plane shear mode fracture. In this work, mode II fracture behavior of concrete specimens, reinforced with pultruded FRP, was investigated by the authors. Shear tests were performed by using both conventional equipment and a non-contact optical technique, Digital Image Correlation (DIC). Starting from the experimental data, the evaluation of the J-integral and of specimens' fracture toughness was carried out. Subsequently, a cohesive law was associated to the J-integral and thus identified by comparison with experimental data, by means of the theoretical approach proposed by Rice. The proposed cohesive zone (CZ) model can be adopted in a Finite Element (FE) code for simulating the debonding failure in composite structures.